The Koak Kaok (Philemon buceroides) Preference for Food Types in Its Natural Habitat on Moyo Island - M. Yamin; I Gde Mertha; I Putu Aryatasa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This research aims to; 1) obtaining a comprehensive and accurate description of the type, composition, and nutritional content of Philemon buceroides food in its natural habitat, 2) the basis for preparing pellets, and 3) input for conservation efforts. Identification and analysis the types of materials that birds eat using a light microscope and a scanning electron microscope (SEM). The composition and chemical content of food nutrients were analyzed using the Kjedhal Gunning Method (AOAC, 1970). As a result, there are two kinds of food for Philemon buceroides, sourced plant parts and insects. Food in the form of plant parts is nectar and fruit from 9 species, 7 species providing food in the form of fruit and two species providing nectar. It eats seven types of insects, that is Diptera, Cryptotympanus accuta, Hymenoprera, Kampi neurobasis, larvae, Orthoptera and Oecophyla samaradigna. The composition and nutritional content of the food consists of 4 types, namely protein 36.8%, carbohydrates 29.6%, fat 20.73%, fiber, vitamin A, vitamin B, vitamin C, and various minerals and water 10 - 76%.